The Effect of Wordwall Media on Junior High School Students’ Narrative Writing Outcomes - Khorin Nisa Ritonga; Ridho Kurniawan; Asri Yulianda (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to determine the effect of using Wordwall application-based learning media on students' learning outcomes in writing narrative texts. The research used a quasi-experimental method with a nonequivalent control group design. The sample consisted of 60 students from MTS Al Ijtimaiyah Siluman, selected through purposive sampling, with 30 students in class VIII-1 as the experimental group and 30 students in class VIII-2 as the control group. The experimental class was taught using Wordwall application-based media, while the control class received conventional instruction. Data were collected using objective test questions designed to assess students’ understanding of narrative text structure and language features. The results showed that students in the experimental group achieved an average posttest score of 80.15, whereas the control group scored an average of 70.15, indicating a 10-point difference. To test the significance of this difference, the Mann-Whitney test was used, resulting in a Sig. (2-tailed) value of 0.003, which is less than the significance level of 0.05. This result confirms that the improvement in learning outcomes was statistically significant. Therefore, it can be concluded that the use of Wordwall application-based media positively influences students' ability to write narrative texts. The findings suggest that interactive, gamified learning tools like Wordwall not only enhance student engagement but also improve mastery of writing skills in a meaningful way. These results highlight the potential of digital learning applications to support more effective and student-centered instruction, particularly in language learning contexts. Teachers are encouraged to integrate such digital tools into their writing lessons to foster improved outcomes in students’ writing performance.